2017
DOI: 10.1016/j.fuel.2016.10.036
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of solar fuels obtained from beech wood solar pyrolysis

Abstract: h i g h l i g h t s Solar pyrolysis of beech wood was carried out with temperature from 600 to 2000°C. Solar fuels (gas, char and oil) were characterized at different temperatures. High temperature favors the tar secondary reaction into H 2 and CO formation. The char and oil characterization highly depends on pyrolysis temperature. The biomass energy is 38-53% upgraded by the solar pyrolysis process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 100 publications
(30 citation statements)
references
References 48 publications
0
30
0
Order By: Relevance
“…The temperature is in the range from 300 to 1000 • C [469]. The heat required can be provided by solar radiation concentrated by solar collectors [470]. Thermodynamic and kinetic conditions, including temperature, heating rate and residence time, determine the nature and composition of products.…”
Section: Pyrolysismentioning
confidence: 99%
“…The temperature is in the range from 300 to 1000 • C [469]. The heat required can be provided by solar radiation concentrated by solar collectors [470]. Thermodynamic and kinetic conditions, including temperature, heating rate and residence time, determine the nature and composition of products.…”
Section: Pyrolysismentioning
confidence: 99%
“…However, they reduce to 1.43 and 0.34 mol/kg of wood, respectively. It is mainly due to the enhancement of their own cracking reaction and steam reforming reaction as temperature increase from 1000 C to 1600 C, which dominates their degradation mechanisms [21,41].…”
Section: Pyrolysis Gas Composition and Lhvs At Different Temperaturesmentioning
confidence: 99%
“…The temperature and heating rate drastically affects the final product distribution and gas composition during solar pyrolysis of raw biomass [16]. The gas product especially H 2 and CO yield significantly increased with temperature (from 600 to 1600 C) and heating rate (from 5 to 50 C/s) mainly due to the enhanced secondary tar reactions [21]. Besides, temperature and heating rate are known to affect HMs transformation during conventional pyrolysis of contaminated biomass [3].…”
Section: Introductionmentioning
confidence: 99%
“…Using a statistical analysis, the authors found the optimum values of the studied variables for producing maximum gas lower heating value. Zeng et al studied the effects of water content, pyrolysis temperature, and heating rate on the product distribution of the solar pyrolysis of beech wood and concluded that a high water content in feedstock led to the formation of a gas‐rich in CO and H 2 . Fuels also obtained from beech wood solar pyrolysis were characterized by Zeng et al, who reported an upgrading of biomass energy higher than 50% at 900°C, indicating the successful solar energy storage in chemical form. Hijazi et al investigated the use of heterogeneous photocatalysts in the solar pyrolysis of waste rubber tires.…”
Section: Introductionmentioning
confidence: 99%